Training on The Use of Artificial Intelligence for Students of SMAN 1 Karangreja, Purbalingga - Ekawati, Anita Dewi; Komara, Cahya (Universitas Muhammadiyah Jember, 2025)
Artificial intelligence (AI) in the field of education has many varieties such as Chat GPT, Consesus, Duolingo, DeepL Translate, QuillBot, Gemini, and many others. The use of artificial intelligence for the digital native generation is not complicated. This generation was born in the digital era with rapid technological advances. Therefore, it is expected that with their abilities, they can easily understand the use of AI. This service provides a deep understanding of how to use and write it in scientific writing to several students of SMAN 1 Karangreja who are trainees. A total of 20 students representing class X to class XII became trainees. In addition, this service also instilled how the impact of AI should be avoided. This service was carried out for two days using the lecture method as a form of interaction with the trainees. The trainees seemed enthusiastic as seen from the many questions they asked. In addition, they can write sentences with the help of AI in a sequential, systematic manner and adopt from the many references provided by AI. Training on the use and impact of AI should be increasingly socialized to schools in the regions. However, it is necessary to pay attention to infrastructure barriers in the regions.